2005
DOI: 10.4321/s1130-01082005001100007
|View full text |Cite
|
Sign up to set email alerts
|

Refractory hepatic hydrothorax: successful treatment with octreotide

Abstract: We report the case of a patient that developed hepatic hydrothorax as the first complication of liver cirrhosis. Due to the lack of response to diuretics, pleurodesis and TIPS, treatment with octreotide was started with resolution of hydrothorax. To the best of our knowledge, this is the third reported case of refractory hepatic hydrothorax with complete and sustained response to octreotide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…There are currently no large studies or randomized trials that have examined these medications in HH, and evidence is largely limited to case reports or case series. (37)(38)(39)(40) Splanchnic and peripheral vasoconstrictors including octreotide, midodrine, and terlipressin increase effective arterial volume and decrease activation of the renin-angiotensin-aldosterone (RAA) system, increasing renal sodium excretion.…”
Section: Other Medical Therapy: Splanchnic and Peripheral Vasoconstrictorsmentioning
confidence: 99%
“…There are currently no large studies or randomized trials that have examined these medications in HH, and evidence is largely limited to case reports or case series. (37)(38)(39)(40) Splanchnic and peripheral vasoconstrictors including octreotide, midodrine, and terlipressin increase effective arterial volume and decrease activation of the renin-angiotensin-aldosterone (RAA) system, increasing renal sodium excretion.…”
Section: Other Medical Therapy: Splanchnic and Peripheral Vasoconstrictorsmentioning
confidence: 99%
“…The amount of fluid in the pleural cavity decreased after the fifth day. During a six-month period of observation, there was no relapse of HH[ 24 ]. The positive effect of octreotide can be explained by its ability to suppress the activation of the renin-angiotensin-aldosterone system induced by diuretics, as well as to increase the excretion of Na + and water[ 25 ].…”
Section: Treatment Of Hhmentioning
confidence: 99%
“…A recent report of a case showed that terlipressin, a drug known to be beneficial in hepatorenal syndrome, might also be effective in the treatment of hepatic hydrothorax 49 . The successful use of octreotides 50,51 and nasal continuous positive airway pressure 52 have also been reported. However, studies in series of patients are needed to confirm these findings.…”
Section: Managementmentioning
confidence: 99%